Plant Regeneration of Pummelo cv. Cikoneng from Cotyledon and Epicotyl - Saraswati Dewi, Iswari; Rahman, I. H.; Purwoko, Bambang Sapta (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2013)
In vitro conservation needs highly efficient micropropagation protocol. The objective of the research was to obtain an efficient and reproducible protocol for pummelo (Citrus maxima(Burm.) Merr.) micropropagation through direct shoot formation. The experiment was arranged in a completely randomized design with two factors and 20 replications. The 1stfactor was type of explant, i.e. cotyledon and epicotyl segments of Pummelo cv. Cikoneng, while the 2ndfactor was the media composition as follow (1) MS + 1.0 mg BAP L-1 + 0.5 mg Kinetin L-1 + 0.5 mg NAA L-1; (2) MS + 2.0 mg BAP L-1 + 0.5 mg Kinetin L-1 + 0.5 mg NAA L-1; (3) MS + 1.0 mg BAP L-1 + 1.0 mg Kinetin L-1 + 0.5 mg NAA L-1; (4) MS + 2.0 mg BAP L-1 + 0.5 mg Kinetin L-1+ 1.0 mg NAA L-1; (5) MS + 2.0 mg BAP L-1+ 1.0 mg Kinetin L-1 + 1.0 mg NAA L-1. Observation was conducted on days to shoot induction, number of explant forming shoots, shoot height, number of shoots, leaves, and roots. The results showed that adventitious shoots emerged from callus in epicotyl (6-8 WAP), but adventitious shoots could emerge directly without an intervening callus phase from cotyledon (4-5 WAP). Shoots emerged from epicotyl were weak and vitrous due to hyperhydricity, thus they can not be used for micropropagation. Cotyledons cultured in media MS + 1.0 mg BAP L-1 + 0.5 mg Kinetin L-1 + 0.5 mg NAA L-1or media MS + 1.0 mg BAP L-1 + 1.0 mg Kinetin L-1 + 0.5 mg NAA L-1gave the highest percentage of explant forming adventitious shoot (38.8 and 26.3%), highest efficiency of shoot formation (62.5 dan 72.5%), and highest numbers of leaves (value of 1.9 leaves shoot-1) and roots (1.1 roots shoot-1) compared to other media. Since shoot height and number of leaves and root were not significantly different in both media, thus cotyledon and media MS + 1.0 mg BAP L-1 + 0.5 mg Kinetin L-1+ 0.5 mg NAA L-1which was less in Kinetin is suggested to be used for pummelo micropropagation.Keywords: Citrus maxima, epicotyl, cotyledon, regeneration, pummelo